Androgen upregulates NR4A1 via the TFAP2A and ETS signaling networks. (August 2019) - Song, Jie; Diao, Feiyang; Ma, Xiang; Xu, Siliang; Cui, Yugui; Jiang, Shiwen; Liu, Jiayin
Highlights: For the first time, NR4A1 transcript variants were identified in human granulosa cells (KGN cell line). Two promoter regions at downstream of NR4A1 TSS were identified which is a vary rare phenomenon in gene transcription regulation. For the first time, the view of ETS family involving in the pathological changes of PCOS characterized with hyperandrogen was proposed. Abstract: Hyperandrogenism is one of the clinical and biochemical characteristics of polycystic ovary syndrome (PCOS). Our previous studies confirmed that nuclear receptor subfamily 4 group A member 1 (NR4A1), as a differentially expressed gene in the ovaries of PCOS patients, was upregulated by increased androgen. However, the potential mechanism of NR4A1 upregulation remains unknown. To elucidate the molecular mechanisms involved in NR4A1 regulation, we cloned and characterized the promoter regions of the NR4A1 gene using a series of truncated promoter plasmids in luciferase reporter assays. We identified two unique core promoters of NR4A1 located within the +1055/+1251 and +3183/+3233 regions relative to the transcription start site. TFAP2A downregulated NR4A1 expression, while five ETS transcription factors, ETS1, ELK1, ERG, FLI1 and SPI1, could upregulate NR4A1 promoter activity in HeLa cells. Of these transcription factors, ETS1 and ELK1 were the most effective ones. Moreover, all six transcription factors were confirmed to interact directly with the NR4A1 promoter. In conclusion, this study presents the first description that TFAP2A and ETS family signaling networks are involved in the androgen-mediated transcriptional regulation of NR4A1, which contributes to the understanding of the molecular mechanisms involved in the TFAP2A-NR4A1 and ETS-NR4A1 signaling networks in PCOS.